Discovery of Novel Inhibitors and Fluorescent Probe Targeting NAMPT - Wang, Xia (Sci Rep, 2015)
Nicotinamide phosphoribosyltransferase (NAMPT) is a promising antitumor target. Novel NAMPT inhibitors with diverse chemotypes are highly desirable for development of antitumor agents. Using high throughput screening system targeting NAMPT on a chemical library of 30000 small-molecules, we found a non-fluorescent compound F671-0003 and a fluorescent compound M049-0244 with excellent in vitro activity (IC(50): 85 nM and 170 nM respectively) and anti-proliferative activity against HepG2 cells. These two compounds significantly depleted cellular NAD levels. Exogenous NMN rescued their anti-proliferative activity against HepG2 cells. Structure-activity relationship study proposed a binding mode for NAMPT inhibitor F671-0003 and highlighted the importance of hydrogen bonding, hydrophobic and π-π interactions in inhibitor binding. Imaging study provided the evidence that fluorescent compound M049-0244 (3 μM) significantly stained living HepG2 cells. Cellular fluorescence was further verified to be NAMPT dependent by using RNA interference and NAMPT over expression transgenic mice. Our findings provide novel antitumor lead compounds and a “first-in-class” fluorescent probe for imaging NAMPT.